Global regulatory standards in environmental and health disputes : regulatory coherence, due regard, and due diligence - Foster, Caroline E., 1969- (Oxford : Oxford University Press, 2021)
This text explores the role played by international courts and tribunals in the development of global regulatory standards. Focusing on regulatory coherence, due regard for the rights of others, and due diligence in the prevention of harm, the book considers how such standards represent a new relationship between domestic and international law.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 8, 2021).
Keywords: Environmental law, International; Environmental law -- International cooperation; International and municipal law